Modeled economic potential for Eucalyptus spp. production for jet fuel additives in the United States. (December 2020) - Davis, Maggie R.; Kainer, David; Tuskan, Gerald A.; Langholtz, Matthew H.; Hellwinckel, Chad M.; Shedden, Magen; Eaton, Laurence
Abstract: Feedstock price and availability remain a barrier to adoption of cellulosic biofuels. Eucalyptus spp., can produce an energy-dense terpene suitable for high-density synthetic hydrocarbon-type fuel (grade JP-10) production in addition to cellulosic-based feedstock for traditional jet fuels (e.g., grade Jet A) and gasoline. This study modeled economic potential for Eucalyptus to fulfill US fuel markets. Cold-tolerant Eucalyptus was simulated in an annual coppice system for maximized leaf production. Results of the lowest simulated price (110 t −1 ) show that within 10 years, there is potential to produce 204 million L yr −1 of fuel, including 51 million L yr −1 of JP-10-type fuel, 75 million L yr −1 of Jet A type fuel, and 77 million L yr −1 of gasoline. These quantities of fuel could be valued at approximately 500 million (USD), with feedstock costs totaling approximately 100 million (USD). Longer-term markets (to 20 years) or higher priced (to 220 t −1 ) scenarios show potential for more production. Research to determine potential for genetic improvement, delivered fuel costs, and biorefinery siting near existing infrastructure is recommended. Highlights: Economic potential for Eucalyptus spp. to fulfill US terpene and cellulosic fuel markets. Annual coppice potential to produce 14.4 dry Mg ha −1 yr −1 . Production at 204 million L yr −1, valued at 500 million (USD), in 10 years.